Trace Detection Towards 2,4,6-Trinitro Phenol at Surface of TiO2 Nanoparticles Based on Fluorescence Resonance Energy Transfer - Chen, Hong; Gao, Daming; Chen, Ling; Li, Yu (Asian Journal of Chemistry, 2012)
This paper reports a resonance energy transfer-fluorescence quenching of 4-methyl coumarin at the surface of titanium dioxide nanoparticles for the ultrasensitive and ultratrace detection of 2,4,6-trinitro phenol in solution environments. The fluorescence resonance energy transfer-based nanoparticle sensors with high fluorescence brightness were synthesized by covalently linking a hybrid monolayer of dye and amine onto the surface of titanium dioxide nanoparticles through alkoxysilane coupling reactions. The linear range is 1 × 10-4-10-5 moL L-1 with a detection limit of 1 × 10-11 moL L-1 and the fluorescence quenching constants of 4-methyl coumarin-APTS-TiO2 nanoparticles towards 2,4,6-trinitrophenol is 2.322 × 104 moL-1 L, which is much larger than those with 2,4,6-trinitro toluene, 2,4-dinitro toluene and nitro benzene, respectively. The results show that the novel strategy is ultrasensitive for the trace detection of 2,4,6-trinitro phenol.